Demonstrating Evidence of Acceptability: The "Catch‐22" of Pediatric Formulation Development. Issue 5 (26th July 2013) - Ranmal, S; Tuleu, C
<x xml:space="preserve">Abstract</x> Both researchers and practitioners have reached an influential period in the new era of developing pediatric medicines. Evolving regulatory reforms and guidance continue to serve as platforms steering research and development while distinctive opportunities and challenges in the field emerge. An advancing research need involves gaining a better understanding of end‐user requirements and acceptability of formulations. This review considers solid oral forms to demonstrate the importance of such research to stakeholders in policy and practice. Clinical Pharmacology & Therapeutics (2013); 94 5, 582–584. doi:10.1038/clpt.2013.154